2017
DOI: 10.1212/wnl.0000000000004648
|View full text |Cite
|
Sign up to set email alerts
|

Association between percent decline in serum total homocysteine and risk of first stroke

Abstract: NCT00794885.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
46
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 63 publications
(50 citation statements)
references
References 26 publications
4
46
0
Order By: Relevance
“…The two recent meta‐analyses also reported that tHcy‐lowering therapy is effective in the prevention of stroke. Furthermore, it has been suggested that percent lowering in tHcy was significantly associated with a reduction in first stroke risk and may possibly serve as a useful indicator for folic acid treatment efficacy on stroke prevention . Consistently, our previous meta‐analysis suggested that there was a significant dose‐response relationship between the percent reduction of tHcy and the decrease in carotid intima‐media thickness, and a greater beneficial effect associated with folic acid therapy was seen in those trials with a larger Hcy reduction (≥30%) .…”
Section: Introductionsupporting
confidence: 74%
See 1 more Smart Citation
“…The two recent meta‐analyses also reported that tHcy‐lowering therapy is effective in the prevention of stroke. Furthermore, it has been suggested that percent lowering in tHcy was significantly associated with a reduction in first stroke risk and may possibly serve as a useful indicator for folic acid treatment efficacy on stroke prevention . Consistently, our previous meta‐analysis suggested that there was a significant dose‐response relationship between the percent reduction of tHcy and the decrease in carotid intima‐media thickness, and a greater beneficial effect associated with folic acid therapy was seen in those trials with a larger Hcy reduction (≥30%) .…”
Section: Introductionsupporting
confidence: 74%
“…Furthermore, it has been suggested that percent lowering in tHcy was significantly associated with a reduction in first stroke risk and may possibly serve as a useful indicator for folic acid treatment efficacy on stroke prevention. 13 Consistently, our previous meta-analysis suggested that there was a significant dose-response relationship between the percent reduction of tHcy and the decrease in carotid intima-media thickness, and a greater beneficial effect associated with folic acid therapy was seen in those trials with a larger Hcy reduction (≥30%). 14 Possible mechanisms by which tHcy causes vascular damage include inhibiting endothelial cell growth, inducing endothelial dysfunction, and promoting vascular remodeling.…”
Section: Introductionsupporting
confidence: 69%
“…Furthermore, a significant positive dose-response association has been found between degree of tHcy reduction and systolic blood pressure (SBP) reduction (6) , and decrease in CVD (7) or carotid intima-media thickness (8) . Consistently, a recent study found that the lowering of tHcy was significantly associated with a reduction in first stroke risk, and may possibly serve as a useful indicator for the use of folic acid therapy in the prevention of stroke (9) .…”
supporting
confidence: 56%
“…41 A recent meta-analysis has concluded that serum homocysteine levels are elevated in patients with BD even during the euthymic state. 47 In our study, the mean serum levels of homocysteine in either LOBD or EOBD group were actually above 11 umol/L and therefore may account for the link to cognitive dysfunctions. In the studies of elderly general population, the serum levels of homocysteine over 11 umol/L were found to be associated with the increased risk of dementia and atrophy of medial temporal lobe.…”
Section: Discussionmentioning
confidence: 39%
“…43,44 The elevated levels of homocysteine potentially lead to cognitive dysfunctions due to the activations of inflammatory and oxidative stress pathways or the reactivations of cholinergic metabolism 45,46 as well as being a potential vascular risk factor itself. 47 In our study, the mean serum levels of homocysteine in either LOBD or EOBD group were actually above 11 umol/L and therefore may account for the link to cognitive dysfunctions.…”
Section: Discussionmentioning
confidence: 39%